ANALISIS KESIAPAN PEMERINTAH DESA DALAM PENGELOLAAN KEUANGAN DAN ASET DESA - Muten Nuna; Arifin Tumuhulawa; Nirmala A Sahi; Lisnawati Pauweni; Ahiar Biongan (Governance, 2023)
The problems faced by the Village Government of Panca Karsa I Taluditi District are related to the management of village finances and village assets. Among them, the readiness of the Human Resources (HR) owned by the Panca Karsa I Village Government in managing village finances and assets. This is also due to the unpreparedness of the village officials in line with developments and changes in regulations and also the lack of reliable human resources in their fields. This qualitative descriptive research by prioritizing primary data and secondary data, focuses on seeing how prepared the village government is in managing village finances and assets, in Panca Karsa I Village, Taluditi District and what factors influence it? The conclusion is that the readiness of the village government of Panca Karsa I, Taluditi District, in general, is quite good, where the village government has a fairly good mental and emotional attitude, namely having the ability and great will to manage village finances and assets. The several factors that influence it are: organizational commitment, human resources and information systems.